Perancangan Sistem Kendali Konveyor dan Sistem Sortir Menggunakan Motor Servo pada Alat Sortir Barang Menggunakan Barcode dengan Web - Muhammad Risqi Nuryana; Ullinuha Latifa (Universitas Islam Lamongan, 2022)
In modern times and advanced technology like today, freight forwarding services or expedition services are in great demand by the people of Indonesia, especially for people who are consumptive and like everything that is easy and practical in meeting the needs of daily life, one of which is the online shopping trend. . With the increase in online shopping, of course, it will affect expedition services, one of which is the accumulation of goods. Due to the large accumulation of goods, we often encounter errors in sorting or classifying goods on expedition services which cause delays in delivery and customer trust. Therefore, an automatic sorting machine is very useful to overcome these problems. By adding a conveyor to the sorting machine, it will certainly simplify the sorting system and also its distribution. By using the on/off control method on the conveyor and proportionally on the sorting system, it will certainly make it easier to operate the sorting machine. A conveyor driven by a 12 V DC motor is sufficient to assist the sorting process with a maximum load of 2 Kg. Then the use of the servo motor type MG996R is the most effective in the sorting process because it is able to sort items that weigh 2 Kg.